Normalizing HDAC2 Levels in the Spinal Cord Alleviates Thermal and Mechanical Hyperalgesia After Peripheral Nerve Injury and Promotes GAD65 and KCC2 Expression - Ouyang, Bihan; Chen, Dan; Hou, Xinran; Wang, Tongxuan; Wang, Jian; Zou, Wangyuan; Song, Zongbin; Huang, Changsheng; Guo, Qulian; Weng, Yingqi (Frontiers in Neuroscience, 2019)
Neuropathic pain is a worldwide health concern with poor treatment outcomes. Accumulating evidence suggests that histone hypoacetylation is involved in development and maintenance of neuropathic pain. Thus, many natural and synthetic histone deacetylase (HDACs) inhibitors were tested and exhibited a remarkable analgesic effect against neuropathic pain in animals. However, studies evaluating specific subtypes of HDACs contributing to neuropathic pain are limited. In this study, using the chronic constriction injury (CCI) rat model, we found that mRNA and protein levels of HDAC2 were increased in the lumbar spinal cord of rats after sciatic nerve injury. Intrathecal injection of TSA, a pan-HDAC inhibitor, suppressed the increase in HDAC2 protein but not mRNA, and showed a dose-dependent pain-relieving effect. By introducing HDAC2-specific shRNA into the spinal cord via a lentivirus vector, we confirmed that HDAC2 mediates mechanical and thermal hyperalgesia after nerve injury. Further examination found two essential participants in neuropathic pain in the inhibitory circuit of the central nervous system: GAD65 and KCC2 were increased in the spinal cord of CCI rats after HDAC2 knockdown. Thus, our research confirmed that HDAC2 was involved in mechanical and thermal hyperalgesia induced by peripheral nerve injury. Furthermore, GAD65 and KCC2 were the possible downstream targets of HDAC2 in pain modulation pathways.